Platelet-derived growth-factor requirements for in vitro proliferation of normal and malignant mesenchymal cells. - Currie, G. A. (Nature Publishing Group, 1981)
Serum obtained by clotting whole blood contains a potent mitogen with apparent specificity for mesenchymal cells. This peptide wound-healing hormone, derived from platelets, is known as platelet-derived growth factor (PDGF). Serum obtained by clotting plasma contains no detectable growth-promoting activity for fibroblasts, and is therefore a valuable additive to culture medium for an examination of the autonomy of cells from exogenous PDGF. Fibroblasts from man, mouse and hamster remain mitotically quiescent in plasma-derived serum and proliferate only when a source of PDGF is added. Normal human kidney epithelial cells and human T-cells proliferate normally in plasma-derived serum, and are unaffected by the addition of PDGF. A range of virally transformed cells and malignant cells from chemically induced rodent sarcomas was tested for their proliferative capacity in plasma-derived serum and their response to exogenous PDGF. A complete spectrum of PDGF-dependence was revealed. Polyoma-transformed BHK21 cells and SV40-transformed 3T3 cells showed complete PDGF independence. Cells from 7 chemically induced rat or mouse sarcomas provided results which ranged from the FS6 (a C57BL Cbi mouse sarcoma which was completely PDGF dependent) to MC28 (a hooded rat sarcoma) which was completely PDGF independent. The dependence of proliferation of these cells on PDGF showed a close correlation with several features of their in vivo behaviour. Tumours which were non-immunogenic in syngeneic hosts, contained few host macrophages and produced a high incidence of spontaneous distant metastases provided PDGF-independent cells. Cells from highly immunogenic, macrophage-rich "non-metastasizing" tumours were on the other hand PDGF dependent and tumours of intermediate "malignancy" provided cells with partial autonomy from PDGF. An assay for anchorage-independent growth provided data which also correlated with autonomy from PDGF. However, daily addition of large amounts of PDGF to BHK21 C13 cells induced reversible anchorage independent growth. The value of plasma-derived serum for the investigation of the proliferative autonomy of malignant cells is emphasized.